Perception Analysis of Service Quality IT Operation Study Case Of PT XYZ - Oyu Mulia Sukmana; Judijanto Judijanto; Adithya Sudiarno (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
Customer satisfaction of IT service delivered by PT XYZ has become essential. Attention to develop an adequate level of customer satisfaction index in Oil and Gas Company and also to assist ICT management for continous improvement of strategy and action to meet Stakeholders needs. Using quantitative research and method Servqual questionair within five (5) variable known as Tangible, Reability, Responsiveness, Assurance and Empathy to analyze Perception an Expectation from IT Users. The result of data processing assisted with SPSS 22 to validate test and reliability of the data. Based on the research result, was obtained average value Servqual Score of Gap 5 is -0.012 on varible Assurance, which means consumers are not satisfed with the exiting service by ICT Department. In Variable of Assurance, concluded that courtesy has the highest score represent of the statement